Filles du peuple ? Pour une stylistique de la chanson au XIXe siècle - Benini, Romain (Signes, 2021)
Songs play a key role in 19th-century literary thinking: Chateaubriand, Lamartine, Stendhal, Hugo, Musset, Michelet, Flaubert, Rimbaud, Verlaine: every famous French author wrote about them. Expressions of daily life as well as political writings, be it familiar or hard to grasp, songs remain a fascinating yet understudied subject. This is partly due to their commonly acknowledged status as minor artistic productions. Yet, songs were an essential form of expression of both intimate and collective issues. This study, based on a large set of archival documents, focuses on 19th-century "popular" songs, mainly through social and political songs inspired by contemporary events. Apart from the prolific French songwriter Béranger - whose glory has progressively faded into simply a name -, who wrote those songs? Who sang them? What were their goals, forms, and themes? This book's ambition is threefold. Firstly, it offers a first-ever detailed textual analysis of 19th-century French songs. Secondly, it explains how the now common idea of "popular song" was born in the first half of the century, and how it grew. Finally, this book strives to address a little-known though extremely rich corpus.